Cerita saya - Lim, Goh Tong 1918- (Pelanduk Publications (M) Sdn.Bhd, 2004)
This is a long-awaited book by one of Malaysia's most interesting entrepreneurs. How Tan Sri Lim Goh Tong built Genting Highlands into a world-class resort has been well-publicised. But this is the first time readers are offered an insight into his life and unique approach. His story is an inspiring one: beginning with nothing to his name, turning difficulties into opportunities, acting on brainwaves, taking calculated risks and confounding sceptics through sheer foresight and perseverance. Typically modest, Tan Sri Lim gives an account that is refreshingly original, wryly humorous and moving in its poignancy.